Increasing University Students Intentional Use Of QRIS E-Payment - Herman Paleni; Suyadi Suyadi; Tiara Permata Indah (UNIVED Press, 2025)
This research examines the variables affecting students' intentions to utilize QRIS e-payment, with a focus on students enrolled in Bina Insan University of management program, despite earlier studies on QRIS adoption has made extensive use of the Technology Acceptance Model (TAM), mixed results point to the need for more investigation. Using the Slovin with a margin of error (0.05), a sample of 270 respondents was chosen from the population of 825 students in this research. To make sure the sample was representative, stratified proportional sampling was used. Using structural equation modeling, hypotheses were evaluated. The results of the study show that students' interest in utilizing QRIS is highly influenced by perceived ease of use and perceived risk. However, student enthusiasm in utilizing QRIS was not significantly impacted by perceived usefulness. This result raises the possibility that adoption may not be fueled only by the useful advantages of QRIS. Rather, it emphasizes how important it is for service providers to concentrate on enhancing transaction security and fostering user confidence. Promoting QRIS adoption among students may be more successful if its security features are improved and users worries regarding data security and financial stability are addressed. Future studies should examine how additional elements, such perceived social influence and institutional trust, affect student intentions to utilize QRIS.